2023
DOI: 10.3390/su15043613
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Awareness of Pig and Poultry Farmers on the Potential of Black Soldier Fly (Hermetia illucens) Farming in Kenya

Abstract: Given the need to boost food production while guaranteeing environmental sustainability, the black soldier fly (BSF) (Hermetia illucens (L.), Diptera: Stratiomyidae) is gaining traction worldwide as an alternative protein source. In Kenya, BSF production and its use as a feed component is an emerging business, but farmer awareness of the potential use of BSF in animal feed has received limited attention. This study examined the factors influencing farmer awareness of insect farming and its usefulness as ingred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…This nonresponsive percentage of farmers corroborates with the 47.5% who admitted not having any knowledge about the use of insects as an alternative protein source for poultry. Similar results have been reported by Bulinda et al [25] when the knowledge and willingness of black soldier fly usage as a potential protein source in pig and poultry production in Kenya was investigated. Though 52.5% of poultry farmers admitted to having some form of knowledge about insects as an alternative protein source for poultry, it was rather disappointing to know that only 3.8% of respondents had ever attempted the adoption or use of insect protein, (specifically, Housefly larvae) as an alternative protein source, out of which only 2.5% found it to be desirable or promising (Fig.…”
Section: Resultssupporting
confidence: 88%
“…This nonresponsive percentage of farmers corroborates with the 47.5% who admitted not having any knowledge about the use of insects as an alternative protein source for poultry. Similar results have been reported by Bulinda et al [25] when the knowledge and willingness of black soldier fly usage as a potential protein source in pig and poultry production in Kenya was investigated. Though 52.5% of poultry farmers admitted to having some form of knowledge about insects as an alternative protein source for poultry, it was rather disappointing to know that only 3.8% of respondents had ever attempted the adoption or use of insect protein, (specifically, Housefly larvae) as an alternative protein source, out of which only 2.5% found it to be desirable or promising (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Oil quality primarily depends on its fatty acid composition [10]. Previous studies have found that BSFL oil is rich in saturated fatty acids (SFAs), mainly lauric acid [11,12], which exhibits antioxidant, antibacterial, antiviral, antifungal, and anticancer properties [7,13,14]. These observations are in agreement with those of a recent study showing that BSFL oil has antioxidant activities without causing toxicity in Artemia salina [11].…”
Section: Introductionsupporting
confidence: 77%
“…A high concentration of lauric acid in the BSFL oil indicates its potential use, which is similar to that of coconut oil and palm kernel oil [36]. Several studies have shown that lauric acid has antibacterial, antiviral, antifungal, and anticancer activities [7,13,14]. Moreover, lauric acid is widely used as a raw material for the production of surfactants in the food, cosmetic, shampoo, and pharmaceutical industries [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This not only represents an excellent opportunity for the feed sector, but also for increasing the production of valuable insect components and conferring new properties on final bioproducts derived from BSF. For instance, the amount of lauric acid, which is naturally high in BSF larvae, comprising about 50% of the total fat fraction, is influenced by the feeding substrate provided to the insect, offering the opportunity to boost it to 76% by administering a carbohydrate-rich diet to the larvae (Suryati et al, 2023). 3.…”
mentioning
confidence: 99%